2012
DOI: 10.1073/pnas.1202970109
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity within the simple gut microbiota of the honey bee

Abstract: Animals living in social communities typically harbor a characteristic gut microbiota important for nutrition and pathogen defense. Accordingly, in the gut of the honey bee, Apis mellifera , a distinctive microbial community, composed of a taxonomically restricted set of species specific to social bees, has been identified. Despite the ecological and economical importance of honey bees and the increasing concern about population declines, the role of their gut symbionts for colony healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
775
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 708 publications
(858 citation statements)
references
References 49 publications
(58 reference statements)
25
775
3
4
Order By: Relevance
“…Ambiguously aligned regions and sites, including missing data, were removed from the multiple alignments before phylogenetic tree constructions. For the phylogeny of SLs (Supplementary Figure S5C), multiple alignments of six protein coding genes, alaS, ffh, pyrG, typA, uvrB and uvrC, were concatenated and subjected to a phylogenetic analysis (Engel et al, 2012). All phylogenetic trees were inferred with maximum likelihood method using RAxML v7.2.8 (Stamatakis, 2006).…”
Section: Molecular Phylogenetic Analysesmentioning
confidence: 99%
“…Ambiguously aligned regions and sites, including missing data, were removed from the multiple alignments before phylogenetic tree constructions. For the phylogeny of SLs (Supplementary Figure S5C), multiple alignments of six protein coding genes, alaS, ffh, pyrG, typA, uvrB and uvrC, were concatenated and subjected to a phylogenetic analysis (Engel et al, 2012). All phylogenetic trees were inferred with maximum likelihood method using RAxML v7.2.8 (Stamatakis, 2006).…”
Section: Molecular Phylogenetic Analysesmentioning
confidence: 99%
“…The use of model organisms such as the fruit fly Drosophila melanogaster, the nematode Caenorhabditis elegans, the house mouse Mus musculus and the zebrafish Danio rerio has facilitated understanding of the mechanisms by which certain biological functions of the hosts are modulated by their microbiota (Rawls et al, 2004;Turnbaugh et al, 2006;Cabreiro and Gems 2013;Erkosar et al, 2013). As interest in environmental genomics emerges, the roles of microbiota in the ecology and evolution of an increasing number of non-model organisms are being investigated, revealing a high diversity in the types of effects observed (Fraune and Bosch, 2010;Engel et al, 2012;Koch and Schmid-Hempel, 2011;Brucker and Bordenstein, 2013). Here we present the first experiments addressing the role of microbiota in a crustacean model, Daphnia.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria in this core microbiota consistently include members of the Burkholderiales, Rhizobiales, Xanthomonadales, Opitutales and Pseudomonadales phylotypes (Anderson et al, 2012;Hu et al, 2014;Russell et al, 2009), signifying their importance as stable, autochthonous members of the gut community (Hu et al, 2014;Sanders et al, 2014). These symbionts are likely to have coevolved with their hosts over their evolutionary history (Sanders et al, 2014), and, as shown for symbionts in the termite (Brune & Ohkuma, 2011;Wertz et al, 2012;Wertz & Breznak, 2007b) and honeybee gut (Engel et al, 2012;Engel & Moran, 2013;Kwong & Moran, 2013), likely confer beneficial functions to host nutrition and disease resistance (Dillon & Dillon, 2004).…”
mentioning
confidence: 99%